SILAM and MACC reanalysis aerosol data used for simulating the aerosol direct radiative effect with the NWP model HARMONIE for summer 2010 wildfire case in Russia. (November 2015) - Toll, V.; Reis, K.; Ots, R.; Kaasik, M.; Männik, A.; Prank, M.; Sofiev, M.
Abstract: Persistent high pressure conditions over the European part of Russia during summer 2010 were responsible for an extended period of hot and dry weather, creating favourable conditions for severe wildfires. The chemical transport model SILAM is used to simulate the dispersion of smoke aerosol for this case. Aerosol fields from SILAM are compared to the Monitoring Atmospheric Composition and Climate (MACC) reanalysis. Moreover, the model output is compared to in situ and remote sensing measurements, paying particular attention to the most intense fire period of August 7 to 9, when the plume reached the Baltic countries and Finland. The maximum observed aerosol optical depth was more than 4 at 550 nm during this time. The aerosol distributions from the SILAM run and the MACC reanalysis are subsequently used in meteorological simulations using the Hirlam Aladin Research for Mesoscale Operational Numerical Weather Prediction in Euromed (HARMONIE) model. The modelling results show a significant reduction of the daily average shortwave radiation fluxes at the surface (up to 125 W/m 2 ) and daily average near-surface temperature (up to 4 °C) through the aerosol direct radiative effect. The simulated near-surface temperature and vertical temperature profile agree better with the observations, when the aerosol direct radiative effect is considered in the meteorological simulation. The boundary layer is more stably stratified, creating poorer dispersion conditions for the smoke. Highlights: Direct radiative effect of summer 2010 Russian wildfires was studied. SILAM model was used for simulating dispersion of the smoke aerosol. Aerosol direct radiative effect in HARMONIE agrees with other studies about the case. Meteorological forecast was improved in the heavily polluted region.